Shore temple in Mamallapuram - Temples of India Project Team (Jio Institute, 2024)
An open-air ambulatory was provided for each tier, hidden in the recession of the next storey by the parapet enclosure of the kutas and the shalas. Image courtesy: Wikimedia Commons